The Jurassic (Pliensbachian to Kimmeridgian) palynology of the Algarve Basin and the Carrapateira outlier, southern Portugal - Borges, Marisa (2014)
The palynology of the Jurassic (Upper Pliensbachian to Lower Kimmeridgian) fill of the Algarve Basin and the Carrapateira outlier, southern Portugal was investigated. Samples were collected from Armação Nova Bay, Mareta Beach, Cilheta Beach and the Carrapateira outlier. At Armação Nova Bay the Upper Pliensbachian–Lower Toarcian succession proved barren, or yielded sparse, non age-diagnostic palynomorphs. Dinoflagellate cysts are confined to the Upper Bajocian to Upper Callovian sedimentary rocks exposed at Mareta and Cilheta beaches and the Lower Kimmeridgian strata of the Carrapateira outlier. At Mareta Beach, the Upper Bajocian, Bathonian and Callovian produced relatively low to moderate diversity dinoflagellate cyst assemblages. Several key bioevents confirm the Bathonian and Callovian ages of the succession; no age-significant Late Bajocian bioevents were noted. The Upper Callovian of Cilheta Beach yielded moderately diverse dinoflagellate cyst associations dominated by Ctenidodinium spp. Key Late Callovian bioevents confirm the age of this succession. Many familiar marker forms known from northwest Europe were not encountered. No typically Arctic forms were recovered throughout the Upper Bajocian to Callovian of this part of the Algarve Basin. It is clear that there was no significant Late Bajocian to Late Callovian dinoflagellate cyst provincialism within southern and northern Europe and adjacent regions. The Carrapateira outlier yielded a moderately diverse Early Kimmeridgian dinoflagellate cyst flora. The Early Kimmeridgian age assessment based on corals and foraminifera is confirmed. Amphorula and Histiophora are present; these are typical of the Late Jurassic of the Tethyan Realm, and their presence is consistent with Late Jurassic provincialism within Europe. The relatively low diversity nature of these Late Bajocian to Early Kimmeridgian dinoflagellate cyst floras is probably mainly due to the relatively deep water, partially enclosed depositional setting. The partially enclosed nature of this part of the Algarve Basin and the Carrapateira outlier seems to have prevented the free migration of dinoflagellates between southern Portugal and elsewhere in Europe.